The Effect of CHSE Implementation on Visitor Satisfaction in Tourism Attraction - Pratiwi, Ni Nyoman Wiladi; Arianty, Anak Agung Ayu Arun Suwi; Dewi, I Gusti Ayu Melistyari (Institut Pariwisata dan Bisnis Internasional, 2023)
The tourism industry has been substantially affected by COVID-19. The risk posed by the COVID-19 epidemic discourages people from visiting a tourist destination. Cleanliness, Health, Safety, and Environment Sustainability (CHSE) is a strategy created by the Ministry of Tourism and Creative Economy for the tourism sector in Indonesia with the goal of providing security and comfort and restoring traveler confidence following the COVID-19 outbreak. This research's objective is to determine the effect of CHSE application on visitor satisfaction at the Tanah Lot tourist destination. In order to collect data for this study's quantitative methodology, the researcher created a questionnaire with a number of predetermined criteria. The sample used in this study was 100 respondents. The study's data processing employed IBM SPSS version 26 to produce the study's findings. The researcher employed multiple linear regression analysis, descriptive statistical analysis, and hypothesis testing to analyze the data. The results of this study reveal that CHSE has a moderately substantial affect on visitor satisfaction at the Tanah Lot tourist attraction, which is 67.7%. CHSE also has a strong influence on visitor satisfaction at the Tanah Lot tourist attraction. The remaining 32.3% is affected by variables outside the scope of this study. The CHSE variable with the greatest impact on visitor satisfaction at the Tanah Lot tourist site is Environment Sustainability with value Standardized Coefficient Beta in the amount of 0,440. Industri pariwisata sangat terdampak oleh COVID-19. Risiko yang ditimbulkan oleh epidemi COVID-19 membuat masyarakat enggan mengunjungi suatu destinasi wisata. Cleanliness, Health, Safety, and Environment Sustainability (CHSE) merupakan strategi yang dibuat Kementerian Pariwisata dan Ekonomi Kreatif untuk sektor pariwisata di Indonesia dengan tujuan memberikan keamanan dan kenyamanan serta memulihkan kepercayaan wisatawan pasca wabah COVID-19. Tujuan penelitian ini adalah untuk mengetahui pengaruh penerapan CHSE terhadap kepuasan pengunjung destinasi wisata Tanah Lot. Guna mengumpulkan data untuk metodologi penelitian kuantitatif ini, peneliti membuat kuesioner dengan sejumlah kriteria yang telah ditentukan. Sampel yang digunakan dalam penelitian ini sebanyak 100 responden. Pengolahan data penelitian ini menggunakan IBM SPSS versi 26 untuk menghasilkan temuan penelitian. Peneliti menggunakan analisis regresi linier berganda, analisis statistik deskriptif, dan uji hipotesis untuk menganalisis data. Hasil penelitian ini mengungkapkan bahwa CHSE mempunyai pengaruh yang cukup besar terhadap kepuasan pengunjung objek wisata Tanah Lot yaitu sebesar 67,7%. CHSE juga mempunyai pengaruh yang kuat terhadap kepuasan pengunjung di objek wisata Tanah Lot. Sisanya sebesar 32,3% dipengaruhi oleh variabel diluar cakupan penelitian ini. Variabel CHSE yang mempunyai pengaruh paling besar terhadap kepuasan pengunjung di lokasi wisata Tanah Lot adalah Kelestarian Lingkungan dengan nilai Standardized Coefisien Beta sebesar 0,440.